2022
DOI: 10.1002/ejic.202200145
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Surfactants in the Interaction and Hydrolysis of Myoglobin by Zr‐MOF‐808

Abstract: Controlled protein hydrolysis is an important procedure in proteomics applications and is used to aid the understanding of protein structure and function. The hydrolysis of hydrophobic proteins is particularly challenging, as due to their poor solubility the use of surfactants, which typically inactivate natural enzymes, is often required. Such limitations of natural enzymes prompted the development of chemical catalysts for the selective hydrolysis of proteins. In this study, the nanozymatic potential of MOF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…4.6, 13.7, 12.2, and 11.1 kDa (Table 7), with a hydrolysis efficiency of around 63% after 8 days in the absence of any surfactant. 270 However, addition of surfactants affects both the protein structure and the MOF-protein interactions in a rather complex manner and, therefore, the structure of the surfactant used was determined to play an important role in the reaction outcome. The anionic surfactant SDS promoted protein hydrolysis by causing larger protein unfolding (±65% hydrolysis efficiency after 8 days) whereas zwitterionic CHAPS and neutral TX-100 surfactants inhibited hydrolysis by interacting with the MOF's active sites or forming micelles on its surface: around 39% and 31% hydrolysis efficiency after 8 days, respectively.…”
Section: Reactivity Of Moc-based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…4.6, 13.7, 12.2, and 11.1 kDa (Table 7), with a hydrolysis efficiency of around 63% after 8 days in the absence of any surfactant. 270 However, addition of surfactants affects both the protein structure and the MOF-protein interactions in a rather complex manner and, therefore, the structure of the surfactant used was determined to play an important role in the reaction outcome. The anionic surfactant SDS promoted protein hydrolysis by causing larger protein unfolding (±65% hydrolysis efficiency after 8 days) whereas zwitterionic CHAPS and neutral TX-100 surfactants inhibited hydrolysis by interacting with the MOF's active sites or forming micelles on its surface: around 39% and 31% hydrolysis efficiency after 8 days, respectively.…”
Section: Reactivity Of Moc-based Materialsmentioning
confidence: 99%
“…Interestingly, while hydrolysis of myoglobin in the presence of CHAPS merely reduced the hydrolysis efficiency, hydrolysis in the presence of TX-100 caused a different cleavage selectivity. 270 Therefore, the addition of specific types of surfactants can influence both the efficiency and selectivity of protein hydrolysis by MOFs. This is extremely valuable for the development of MOFs as catalysts for protein hydrolysis as it shows that the reactivity of MOFs can be tuned through using additives, such as surfactants, and that the MOF catalyst does not completely lose its activity in the presence of surfactants, unlike natural proteases.…”
Section: Reactivity Of Moc-based Materialsmentioning
confidence: 99%
“…The surface chemistry of the MOF can also be modified by using surfactants to tune the MOF–substrate interactions, without having to resort to linker modifications. Comparing the hydrolysis of horse heart myoglobin (HHM) by MOF-808 in the absence, 92 and in the presence of different surfactants reveals that different fragmentations are obtained due to the altered MOF–protein interactions (Fig. 2).…”
Section: Modifications To the Mof Structure And Its Impact On The Rea...mentioning
confidence: 99%
“…Inspired by metalloproteases that contain Lewis acid metals in their active sites, various metals were combined with suitable organic ligands to form chelating complexes with a high stability and versatile reactivity that can be used for protein hydrolysis among many other biomolecular transformations. , In the past decade, our group has developed polyoxometalates (POMs) as inorganic ligands for metal cations, where the molecular recognition ability of the POM scaffolds toward protein surfaces was combined with hydrolytically active Lewis acid metal cations (Ce­(IV), Zr­(IV), or Hf­(IV)) to catalyze peptide bond hydrolysis. Despite this promising proof of concept, the relatively low reactivity of classical transition metal complexes, prompted the development of nanozymes, i.e., nanomaterials with intrinsic enzyme-like properties. The rapid evolution and growing understanding of nanomaterials allow for the engineering of active centers that mimic those of natural enzymes, resulting in nanomaterials that could address current limitations of natural enzymes. , Despite the remarkable advances in the field, most nanozymes have been designed to exhibit redox activity, mimicking the oxidase/peroxidase family of enzymes. Nanozymes that mimic other types of enzymes, such as proteases, have seen substantially less development in comparison. In this regard, metal–organic frameworks (MOFs) have recently emerged as highly reactive and recyclable catalysts for protein hydrolysis. In particular, MOFs based on Zr­(IV) and Hf­(IV) metal-oxo clusters (MOCs) have been used as catalysts for an array of different biomolecular transformations, including peptide bond hydrolysis, where theoretical studies suggested that MOCs act as the catalytically active sites. ,,, …”
Section: Introductionmentioning
confidence: 99%